Sustainable biofuel strategy in Karnataka state a review. Issue 2 (9th March 2015) - Lokesh, Adappa Chandrashekar; Mahesh, Naranapur Somashekhar; Gowda, Balakrishna; White, Peter
Abstract : Purpose: – The purpose of this paper is to present a review of strategy developed by University of Agricultural Sciences, Bangalore in Biofuel Park, Hassan (Government of Karnataka, initiative to develop biofuel programme in India) for promoting sustainable biodiesel production using oil extracted from tree borne oil species. The main aim of this study was to analyse the current strategy, identify the limitations and propose sustainable biodiesel production strategies for rural Karnataka. Design/methodology/approach: – The paper presents critical analysis of current Biofuel Park strategy using strength weakness opportunities and threat (SWOT) method. The data for SWOT analysis were collected from Biofuel Park log books, followed by interviews with around 50 associations of biofuel feed stock growers. Further, to evolve sustainable strategies, a case study was carried out at a local village assessing sustainability of biodiesel production and use from four local tree species oil namely; Pongamia pinnata, Azadiractha indica, Madhuca indica and Simarouba glauca . The evolved strategies were brainstormed with local farming community and the deliberations were used to lay a road map for implementing the evolved strategies. Findings: – The strategies proposed in the paper would help in sustainability of villages with respect to local energy needs and generate employment. The roadmap proposed would minimise green house gas (GHG) emission compared to Biofuel Park model/strategy and minimise biomass displacement. Originality/value: – This paper fulfils a need to study biofuel strategies adopted by government bodies, analyse the same for sustainability and propose alternatives to overcome the limitations of the practiced strategy.